Unusual Presentation of Lipemia Retinalis Presented with Visual Field Defect: Poster Presentation - Case Report - Resident - Regina Ivanovna; Irma Suwandi Sadikin; Dearaini; Eduard Jordi Luminta; Rina La Distia Nora; Yulia Aziza (Majalah Oftalmologi Indonesia, 2023)
Introduction : Lipemia retinalis is an ocular presentation that associated to hypertriglyceridemia. Most cases are usually asymptomatic, with changes detected only from fundus examination. This case report highlights a case of lipemia retinalis with decreased peripheral visual field. Case Illustration : Thirty four year-old female came with complaint of blurry right eye (RE) 3 months before hospital visit, especially on inferotemporal part of her right eye. She had history of diabetes mellitus and hypertriglyceridemia. Her sister also has known history of hypertriglyceridemia. Ophthalmological examination revealed 6/6 visual acuity on both eyes, with normal anterior segment of both eyes. Fundus examination showed creamy retinal vessels on both eyes. Humphrey perimetry result showed inferotemporal visual field defect of RE. At time of visit, triglyceride level was 1440 mg/dL. Patient was prescribed fenofibrate 1x300 mg daily by Endocrinology Department. After 6 months of fenofibrate therapy, serum triglyceride level was decreasing to 185 mg/dL. Ophthalmology exam revealed a significant decrease of creamy white vessel on right eye and normal vessel of left eye. Humphrey perimetry showed decreased visual field defect Discussion : Hypertriglyceridemia can result from familial or secondary to systemic diseases. Creamy vessel appearance in lipemia retinalis is resulted from presence of triglyceride-laden chylomicrons in the plasma. Lipemia retinalis rarely manifests with reduced peripheral vision, which is presented in this case. Conclusion : Lipemia retinalis is often overlooked due to its asymptomatic nature. Prompt recognition might be live saving from life-threatening condition resulting from hypertriglyceridemia. Triglyceride- lowering drug therapy is very useful in improving peripheral field defect as presented in our case report.